Improving Employee Performance through Organizational Interventions on Personal Competence: An Action Research Study of BTIC in China - Huang, Dunhua; Lu, Lee Hsing (ABAC ODI JOURNAL Vision. Action. Outcome, 2024)
The study investigated the effects of organizational development interventions on Personal Competence such as Perceived Career Development, Management Competence, Affective Commitment, Continuance Commitment and Collaboration Skills to improve team leaders’ Employee Performance in Beijing Tianhai Industrial Co., Ltd (BTIC). The study was conducted on 40 team leaders from production department in BTIC using qualitative and quantitative research methods. Before implementing the OD intervention, the researcher collected data on personal competence such as perceived career development, management competence, affective commitment, continuance commitment, collaboration skills and employee performance through questionnaires and interviews. The OD interventions included project starting, training, coaching, team building, evaluation and feedback. After the intervention, the same questionnaires and interviews were used to gather data, and the changes were compared to evaluate the effectiveness of the ODI. The data collected before and after the ODI were analyzed, and it was found that the data were not normally distributed. The researcher used unary linear regression, and Wilcoxon signed rank to validate the hypotheses. The results indicated that perceived career development, management competence, affective commitment, continuance commitment, collaboration skills and employee performance of the team leaders had significantly improved after the ODI. In conclusion, this study indicates that project starting, training, coaching, team building, evaluation and feedback are effective ODI for enhancing perceived career development, management competence, affective commitment, continuance commitment, and collaboration skills. Furthermore, the study finds that perceived career development, management competence, affective commitment, continuance commitment, and collaboration skills positively correlate with employee performance.